Pengaruh Latihan Interval Terhadap Kecepatan Lari 5000m pada Atlet STC (Sony Training Center) di Brigif 9 Jember - Regita Cahaya Maharani; Rizki Apriliyanto; Ahmad Sulaiman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the effect of interval training on the 5000-meter running speed of athletes at STC Brigif 9 Jember. The research method employed was quantitative with a pre-test and post-test design. The research instrument was the measurement of the 5000-meter running time before and after the interval training program. Descriptive analysis showed that the average running time decreased from 21.87 seconds in the pre-test to 20.68 seconds in the post-test, indicating an improvement in running speed. The paired sample t-test revealed a t-value of 15.392 with a significance level of 0.000 (p < 0.05), confirming a significant difference between pre-test and post-test results. Pearson correlation analysis showed an r-value of 0.802 (p < 0.05), categorized as very strong. Conclusion, that interval training has a substantial and effective impact on enhancing long-distance running performance, particularly in the 5000-meter event. Keywords: interval training, running speed, athletics, 5000 meters